{-# LANGUAGE RebindableSyntax #-} {-# LANGUAGE MultiParamTypeClasses #-} {-# LANGUAGE FlexibleInstances #-} {- | Copyright : (c) Henning Thielemann 2004-2005 Maintainer : numericprelude@henning-thielemann.de Stability : provisional Portability : requires multi-parameter type classes For a multi-set of numbers, we describe a sequence of the sums of powers of the numbers in the set. These can be easily converted to polynomials and back. Thus they provide an easy way for computations on the roots of a polynomial. -} module MathObj.PowerSum where import qualified MathObj.Polynomial as Poly import qualified MathObj.Polynomial.Core as PolyCore import qualified MathObj.PowerSeries.Core as PS import qualified Algebra.VectorSpace as VectorSpace import qualified Algebra.Module as Module import qualified Algebra.Algebraic as Algebraic import qualified Algebra.Field as Field import qualified Algebra.IntegralDomain as Integral import qualified Algebra.Ring as Ring import qualified Algebra.Additive as Additive import qualified Algebra.ZeroTestable as ZeroTestable import Algebra.Module((*>)) import Control.Monad(liftM2) import qualified Data.List as List import Data.List.HT (shearTranspose, sieve) import NumericPrelude.Base as P hiding (const) import NumericPrelude.Numeric as NP newtype T a = Cons {sums :: [a]} {- * Conversions -} lift0 :: [a] -> T a lift0 = Cons lift1 :: ([a] -> [a]) -> (T a -> T a) lift1 f (Cons x0) = Cons (f x0) lift2 :: ([a] -> [a] -> [a]) -> (T a -> T a -> T a) lift2 f (Cons x0) (Cons x1) = Cons (f x0 x1) const :: (Ring.C a) => a -> T a const x = Cons [1,x] {- Newton-Girard formulas, cf. Modula-3: arithmetic/RootBasic.mg s'/s = p -} {- s[k] - the elementary symmetric polynomial of degree k p[k] - sum of the k-th power s[0](x0,x1,x2) = 1 s[1](x0,x1,x2) = x0+x1+x2 s[2](x0,x1,x2) = x0*x1+x1*x2+x2*x0 s[3](x0,x1,x2) = x0*x1*x2 s[4](x0,x1,x2) = 0 p[0](x0,x1,x2) = 1 + 1 + 1 p[1](x0,x1,x2) = x0 + x1 + x2 p[2](x0,x1,x2) = x0^2 + x1^2 + x2^2 p[3](x0,x1,x2) = x0^3 + x1^3 + x2^3 p[4](x0,x1,x2) = x0^4 + x1^4 + x2^4 s(t) := s[0] + s[1]*t + s[2]*t^2 + ... p(t) := p[1]*t + p[2]*t^2 + ... Then it holds t*s'(t) + p(-t)*s(t) = 0 This can be proven by considering p as sum of geometric series and differentiating s in the root-wise factored form. Note that we index the coefficients the other way round and that the coefficients of the polynomial are not pure elementary symmetric polynomials of the roots but have alternating signs, too. -} fromElemSym :: (Eq a, Ring.C a) => [a] -> [a] fromElemSym s = fromIntegral (length s - 1) : PolyCore.alternate (divOneFlip s (PolyCore.differentiate s)) divOneFlip :: (Eq a, Ring.C a) => [a] -> [a] -> [a] divOneFlip (1:xs) = let aux (y:ys) = y : aux (ys - PolyCore.scale y xs) aux [] = [] in aux divOneFlip _ = error "divOneFlip: first element must be one" fromElemSymDenormalized :: (Field.C a, ZeroTestable.C a) => [a] -> [a] fromElemSymDenormalized s = fromIntegral (length s - 1) : PolyCore.alternate (PS.derivedLog s) toElemSym :: (Field.C a, ZeroTestable.C a) => [a] -> [a] toElemSym p = let s' = PolyCore.mul (PolyCore.alternate (tail p)) s s = PolyCore.integrate 1 s' in s toElemSymInt :: (Integral.C a, ZeroTestable.C a) => [a] -> [a] toElemSymInt p = let s' = PolyCore.mul (PolyCore.alternate (tail p)) s s = PolyCore.integrateInt 1 s' in s fromPolynomial :: (Field.C a, ZeroTestable.C a) => Poly.T a -> [a] fromPolynomial = let aux s = fromIntegral (length s - 1) : PolyCore.negate (PS.derivedLog s) in aux . reverse . Poly.coeffs elemSymFromPolynomial :: Additive.C a => Poly.T a -> [a] elemSymFromPolynomial = PolyCore.alternate . reverse . Poly.coeffs {- toPolynomial is not possible because this had to consume the whole sum sequence. -} binomials :: Ring.C a => [[a]] binomials = [1] : binomials + map (0:) binomials {- * Show -} appPrec :: Int appPrec = 10 instance (Show a) => Show (T a) where showsPrec p (Cons xs) = showParen (p >= appPrec) (showString "PowerSum.Cons " . shows xs) {- * Additive -} {- Use binomial expansion of (x+y)^n -} add :: (Ring.C a) => [a] -> [a] -> [a] add xs ys = let powers = shearTranspose (PolyCore.tensorProduct xs ys) in zipWith Ring.scalarProduct binomials powers instance (Ring.C a) => Additive.C (T a) where zero = const zero (+) = lift2 add negate = lift1 PolyCore.alternate {- * Ring -} mul :: (Ring.C a) => [a] -> [a] -> [a] mul xs ys = zipWith (*) xs ys pow :: Integer -> [a] -> [a] pow n = if n<0 then error "PowerSum.pow: negative exponent" else sieve (fromInteger n) -- map head . iterate (List.genericDrop (toInteger n)) instance (Ring.C a) => Ring.C (T a) where one = const one fromInteger n = const (fromInteger n) (*) = lift2 mul x^n = lift1 (pow n) x {- * Module -} instance (Module.C a v, Ring.C v) => Module.C a (T v) where x *> y = lift1 (zipWith (*>) (iterate (x*) one)) y instance (VectorSpace.C a v, Ring.C v) => VectorSpace.C a (T v) {- * Field.C -} instance (Field.C a, ZeroTestable.C a) => Field.C (T a) where recip = lift1 (fromElemSymDenormalized . reverse . toElemSym) {- * Algebra -} root :: (Ring.C a) => Integer -> [a] -> [a] root n xs = let upsample m ys = concat (List.intersperse (List.genericReplicate (m - 1) zero) (map (:[]) ys)) in case compare n 0 of LT -> upsample (-n) (reverse xs) GT -> upsample n xs EQ -> [1] instance (Field.C a, ZeroTestable.C a) => Algebraic.C (T a) where root n = lift1 (fromElemSymDenormalized . root n . toElemSym) {- given the list of power sums @x1^j + ... + xn^j@ and a power series for the function @f@, compute the series approximations of @f(x1) + ... + f(xn)@. -} approxSeries :: Module.C a b => [b] -> [a] -> [b] approxSeries y x = scanl (+) zero (zipWith (*>) x y) {- input lists contain roots -} propOp :: (Eq a, Field.C a, ZeroTestable.C a) => ([a] -> [a] -> [a]) -> (a -> a -> a) -> [a] -> [a] -> [Bool] propOp powerOp op xs ys = let zs = liftM2 op xs ys xp = fromPolynomial (Poly.fromRoots xs) yp = fromPolynomial (Poly.fromRoots ys) ze = elemSymFromPolynomial (Poly.fromRoots zs) in zipWith (==) (toElemSym (powerOp xp yp)) ze -- PolyCore.equal (toElemSym (powerOp xp yp)) ze